2014
DOI: 10.1038/eye.2014.276
|View full text |Cite
|
Sign up to set email alerts
|

Ocular motor abnormalities in neurodegenerative disorders

Abstract: Eye movements are a source of valuable information to both clinicians and scientists as abnormalities of them frequently act as clues to the localization of a disease process. Classically, they are divided into two main types: those that hold the gaze, keeping images steady on the retina (vestibulo-ocular and optokinetic reflexes) and those that shift gaze and redirect the line of sight to a new object of interest (saccades, vergence, and smooth pursuit). Here we will review some of the major ocular motor abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 96 publications
(125 reference statements)
4
61
0
Order By: Relevance
“…Saccadic hypometria, which is considered one of the most consistent ocular motor abnormalities in PD (Antoniades & Kennard, ; Rottach, Riley, DiScenna, Zivotofsky, & Leigh, ) and was discovered in our patients with de novo PD, was not clearly pronounced in iRBD patients. This suggests that hypometria appears later in the disease course, in line with the progression of PD motor signs.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Saccadic hypometria, which is considered one of the most consistent ocular motor abnormalities in PD (Antoniades & Kennard, ; Rottach, Riley, DiScenna, Zivotofsky, & Leigh, ) and was discovered in our patients with de novo PD, was not clearly pronounced in iRBD patients. This suggests that hypometria appears later in the disease course, in line with the progression of PD motor signs.…”
Section: Discussionmentioning
confidence: 51%
“…This is supported by previous studies which showed that poor antisaccade error rate performance correlates with neuropsychological test measures of prefrontal cortical function (Levy, Mendell, & Holzman, ; Postuma, Berg, et al, ; Postuma, Iranzo, et al, ). Higher antisaccadic error rates were also found in early‐stage drug‐naive PD patients (Antoniades & Kennard, ; Antoniades et al, ). Eye movement abnormalities have been presumed to occur even in the pre‐symptomatic phase of neurodegenerative disorders; however, there have been no studies characterizing eye movement metrics in iRBD performed so far (Antoniades & Kennard, ).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…As the neurodegeneration progresses, so does motor disability, manifesting in slowed and small movements (bradykinesia/hypokinesia) and muscle rigidity. Neurodegeneration also affects saccades (2)(3)(4)(5)(6)(7)(8), smooth pursuit eye movements (2)(3)(4)(5)(6)8,9) and visual perception (10). Reduced mobility creates difficulties for perceptual research on PD patients because impaired motor dexterity renders manual responses unreliable.…”
Section: Introductionmentioning
confidence: 99%